Evaluation of the relationship between perception of tobacco packaging pictorial warnings and the nicotine addiction levels of smokers who admitted to smoking cessation clinic in Malatya, Turkey - Beyhan Sağmen, Seda; Özdemir, Mikail (The European Research Journal, 2019)
Objective: In this study, we aimed to investigate relationship between perception of tobacco packaging pictorial warnings and the nicotine addiction levels of smokers who admitted to smoking cessation clinic in Malatya, Turkey. Methods: Three hundred fifty-six patients were enrolled from the Malatya State Hospital Smoking Cessation Clinic. The characteristics of the patients, and number of cigarettes smoked were evaluated. The Fagerström test for nicotine dependence was used. Fourteen of the best-known and most effective pictorial health warnings on cigarette packages were shown and evaluated. Results: The two best-known pictorial warnings in both male and female participants were pictorial 6, “Smoke contains benzene, nitrosamines, formaldehyde, and hydrogen cyanide” and pictorial 7, “Smoking causes fatal lung cancer”. The third best-known pictorial warning for female was pictorial 4, “Smokers die younger,” and for male it was pictorial 1, “Smoking may reduce blood flow and causes impotence”. Female were most affected by pictorial 11, “Protect children; don’t make them breathe your smoke’’, and male were most affected bypictorial 1, “Smoking may reduce blood flow and causes impotence” (p < 0.043 and p = 0.01, respectively). Fagerström scores compared with pictures mostly known and affected by participants, the highest and lowest scores belongs to same pictures; the highest Fagerström score was 8.29 ± 2.14 for best known and 8.25 ± 2.19 for most affected picture is number 2; the lowest Fagerström score was 6.46 ± 2.55 for best known and 6.56 ± 2.68 for most affected picture is number 3. Conclusion: The effect of pictures about the decision to quit smoking may be investigated by a qualitative study especially for pictures 1, 2, 4, 6, 7, and 11.